Fishing in Different Pools: Job-Search Strategies and Job-Finding Success in Canada in the Early 1980s - Osberg, Lars (Journal of Labor Economics, 1993)
This article examines the job-search methods of jobless workers and emphasizes sample selectivity in choice of job-search strategies (especially use of public employment agencies). Longitudinal data from the Labour Force Survey of Canada for 1981, 1983, and 1986 indicate that job-search methods change with the business cycle and that many people find jobs without any reported search. The determinants of job-search success also vary substantially over the business cycle, implying a substantial social return to public employment agencies at the 1983 trough of the recession but no noticeable benefits when aggregate unemployment is relatively low.